Women in science: achievements and ambitions - Delanerolle, G; Riga, E; Thayanandan, T; Griffiths, J; Lawson, J; Roberts, S; Haque, N; Sandle, N; Raymont, V (Mark Allen Group, 2021)
International Women's Day will be celebrated on 8 March 2021. Much has changed in the modern world, but it is still a fact that women are underrepresented in many sectors; this is especially true in science and research. Colleagues from the Oxford Brain Health Clinical Trials Unit reflect on the historical contribution of women in STEM and what future challenges and successes may lay ahead.